The Dynamics of Urban Public Space Perception in the New Normal Era - Yordan Kristanto Dewangga; Sita Yuliastut Amijaya; Hoseo Viadolorosa (Departement of Architecture, Universitas Islam Indonesia, 2021)
The coronavirus pandemic or Covid-19 has happened in several countries, including Indonesia. This condition has an impact not only on public health but also on all sectors. Yogyakarta, a province in Indonesia, receives the impact of this pandemic, especially the Malioboro as a famous public area in the city. The Malioboro area, as an urban public space, becomes quieter due to the coronavirus pandemic. The new normal policy, which the government implemented through the adaptation of new habits, gradually bringing back the activities in the Malioboro area. Health protocols to maintain social distancing keep on encouraged with direct and written persuasive methods. The purpose of this study is to explore people's perceptions of urban public spaces in the new normal era in Malioboro. The method used was conducting a direct survey in Malioboro and giving a closed questionnaire online to the public. The discussion was performed by examining the results of a closed questionnaire with the current situation in Malioboro. The conclusions obtained that the community has received information to maintain social distancing. However, many people ignore the health protocols so that no difference with the situation before the pandemic. This condition does not change the spatial patterns and layouts related to space at the public scale and the distance of social interactions.Keywords: Covid-19; public spaces; social distancing; social interaction